Penerapan Model Pembelajaran PBL Berbantuan Media Interaktif Articulate Storyline 3 untuk Meningkatkan Pemahaman Konsep pada Materi Kalor Kelas XI SMA - Yasmin Pajar, Putri; Azhar; Ernidawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low understanding of students' physics concepts, especially heat material, is the background to this research. The cause is the learning process that still tends to be conventional and does not involve students actively. This study aims to determine the significant differences in students' conceptual understanding between classes that use the Problem Based Learning (PBL) learning model assisted by interactive media Articulate Storyline 3 and classes that apply conventional learning techniques for heat material for grade XI of high school. A quasi-experiment was used as a research method with a posttest only non-equivalent control group design. All grade XI students of SMA Negeri 2 Pekanbaru were the population in the study, with a simple random sampling technique selected as a sample of two classes. A conceptual understanding test in the form of 21 multiple-choice questions was used for data collection. The results of the experimental class produced an average score of 82.66 (categorized as good), higher than the control class which obtained an average of 78.66 (categorized as good). The difference test using the Independent Sample T-Test produced a significance value of 0.031 <0.05, so there was a significant difference in students' conceptual understanding between the two groups. It can be concluded that the application of the PBL model assisted by the interactive media Articulate Storyline 3 is effective in improving students' conceptual understanding of heat material.